The Interest Rate-Exchange Rate Nexus in the Asian Crisis Countries - Ghosh, Atish (IMF Working Papers; Working Paper ;, 2000)
Sharp exchange rate depreciations in the East Asian crisis countries (Indonesia, Korea, and Thailand) raised doubts about the efficacy of increasing interest rates to defend the currency. Using a standard monetary model of exchange rate determination, this paper shows that tighter monetary policy was in fact associated with an appreciation of the exchange rate. Moreover, there is little evidence of higher real interest rates contributing to a widening of the risk premium.